Characterization of an industry-grade CMOS camera well suited for single molecule localization microscopy – high performance super-resolution at low cost. Issue 1 (December 2017) - Diekmann, Robin; Till, Katharina; Müller, Marcel; Simonis, Matthias; Schüttpelz, Mark; Huser, Thomas
Abstract Many commercial as well as custom-built fluorescence microscopes use scientific-grade cameras that represent a substantial share of the instrument's cost. This holds particularly true for super-resolution localization microscopy where high demands are placed especially on the detector with respect to sensitivity, noise, and also image acquisition speed. Here, we present and carefully characterize an industry-grade CMOS camera as a cost-efficient alternative to commonly used scientific cameras. Direct experimental comparison of these two detector types shows widely similar performance for imaging by single molecule localization microscopy (SMLM). Furthermore, high image acquisition speeds are demonstrated for the CMOS detector by ultra-fast SMLM imaging.